Influence of semolina characteristics and pasta-making process on the physicochemical, structural, and sensorial properties of commercial durum wheat spaghetti - Carpentieri, Serena; Larrea-Wachtendorff, Dominique; Ferrari, Giovanna (Frontiers in Food Science and Technology, 2024)
Introduction: This study aimed to investigate the effects of semolina characteristics and pasta-making processing on the quality of durum wheat spaghetti (A, B, and C) using a reverse engineering approach. Methods: Proximate composition, color, granulometry, pasting and thermal properties were determined to characterize semolina, while pasting, thermal and cooking properties, microstructure and sensory profile were evaluated for spaghetti. Results and Discussion: The sensory profile of sample A, in terms of higher yellowness and hardness, lower stickiness, agreed with the higher transition temperatures (60.07–74.6 °C) and enthalpy of amylose-lipid complexes, degree of starch gelatinization, pasting viscosities and compression force, lower water absorption, cooking losses (4.78 g/100 g), and adhesiveness (0.39 N/mm). Moreover, the microstructural analysis showed a network with denser areas, and starch granules strongly embedded in the gluten matrix for sample A with respect to samples B and C. These results might be ascribed to the semolina characteristics. Sample A was richer in starch (71.4%), lipid (1.6%), and protein (14.0%), and the higher drying temperatures affected protein crosslinking, starch organization, cooking properties, and appearance of spaghetti. The approach used in this study could be suitable in gathering the different phenomena occurring in pasta production process which concur to give spaghetti its distinctive quality.